Upaya Guru Bimbingan Dan Konseling dalam Meningkatkan Sikap Sosial Siswa Melalui Pendekatan Client Centered Therapi pada Siswa SMP - Tanod, Mareyke Jessy (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
The problem in this research is the low of positive social attitude of students in because not yet maximal approach of client centered therapi done by teacher of guidance and counseling. The purpose of this study is to know how the efforts of teachers guidance and counseling in improving students 'social attitudes through the Client Centered Therapi approach on students of class VIII SMP Negeri 27 Bandar Lampung Lesson Year 2017/2018 and to determine what factors are constraints in improving students' social attitudes through the Client Centered Therapi approach on the students of class VIII SMP Negeri 27 Bandar Lampung Lesson Year 2017/2018. The method used in this study qualitative descriptive method, the subject of research are three students of class VIII SMP Negeri 27 Lampung Lamp, data collection techniques menggunakn observation techniques, interviews and documentation. Data analysis using the skin's data analysis, data presentation and data verification. Based on the results of research indicate that: (1) The effort of teacher guidance and counseling in improving social attitude through approach of client centered therapi in academic year 2017/2018 was quite effective it can be seen from the change of attitude and behavior experienced by the three subject before and after done client centered counseling. (2) The inhibiting factors in improving students' social attitudes are internal factors derived from BK teachers and students and external factors derived from the family environment, the formal and non formal education environment.